ANALISIS AIR ASAM TAMBANG UNTUK MENGURANGI KADAR SULFUR - Marlia Mamede; Sennahati (Cokroaminoto Journal of Chemical Science, 2023)
The development of coal resources has a negative impact on the environment. Open-pit mining activities and the mine's impact are very serious in terms of Acid Mine Water.This research is conducted to analyze the ability of water hyacinth plants in neutralizing acid mine water To reduce the pH of acid mine drainage and sulfate content, an experimental study was made.In this research, acid mine water comes from coal mining locations in Bone Regency and for water hyacinth plants comes from Borong District Makassar City. This research was conducted with 4 treatments by means of 1 Individual (10%), 3 Individuals (30%), 6 Individuals (60%) and 9 Individuals (90%) with 2 repetitions.The results showed that the water hyacinth plant was able to adsorb acid mine water. Initial results showed a pH of 3.1 after 14 days of treatment showed a pH of 6.5. For the results of sulfate analysis showed that the concentration of 30% had good results with a value of 114.83 mg / L at a surface area of ​​10% and 8.88 mg / L at a surface area of ​​30%, before being treated the Sulfate content value of 272 29 mg / L. From the results of the study showed that surface area and contact time had an effect on reducing sulfate levels and decreasing pH in acidic mine water.